Therapeutic efficacy of treatment measures for strongylidoses of sheep digestive tract - Bondarevskyi, I. (Scientific Progress & Innovations, 2025)
Invasion diseases are the most widespread in the world and cause significant economic losses to the sheep farming. Gastro-intestinal strongylidoses of sheep are among the most relevant. These diseases are mainly chronic and are accompanied by damage to the intestinal and abomasum mucous lining and decrease in animal productivity. Today, anti-helminthic means are used as one of the fastest and most convenient methods of fighting strongyles of sheep digestive tract. However, despite a large choice of such preparations both on the world market and in Ukraine, veterinary specialists are more often noting a decrease in their effectiveness. Previous studies by scientists have shown that the development of resistance in nematodes to anti-helminthic agents is connected with their excessive and uncontrolled use. Therefore, the purpose of the study was to give an assessment of the anti-helminthic efficacy of Closantel 10 %, Doramax and Brovermectin 1 % preparations. The drugs were administered subcutaneously to the animals, once, according to the instructions for their use. The results of the conducted studies show that macrolide-based anti-helminthics (Doramax and Brovermectin 1 %) were more effective than Closantel 10 % (EE – 90.0 %; IE – 95.35 %) in case of the digestive tract strongylidoses on the 7th day of the experiment (EE and IE – 100 %). On the 14th day, the extensive effectiveness and intensive effectiveness of the above mentioned anti-helminthics made 100% in case of the digestive tract strongylidoses. According to our data and the indicators of general clinical observations, it was found that after the application of Closantel 10 %, Doramax and Brovermectin 1%, no side effects were observed in animals during the experiment. However, in the future, it is necessary to pay attention to Closantel 10 % with DR Closantel, since in the near future, helminthes may develop resistance to this preparation. The obtained results will contribute to raising the efficacy of treatment and preventive measures against sheep digestive tract strongylidoses on sheep farms of various forms of ownership.